On short-term institutional trading skill, behavioral biases, and liquidity need - Chakravarty, Sugato; Ray, Rina (Journal of Corporate Finance, 2020)
Are portfolio managers skilled or do they trade too much? Using a marked-to-market based “fair-value” method for measuring fund manager skill, we find that institutional managers can potentially earn +42 (+33) basis points benchmark-adjusted return before transaction costs after a holding period of four weeks on their buy (sell) trades. After transaction costs, the benchmark-adjusted return for the buy (sell) trades is +1 (-8) basis points. Pension fund managers outperform money managers. We are unable to detect evidence for overconfidence among pension fund managers over this short-horizon. In addition, we are unable to find evidence of disposition effect among mutual fund managers. Institutions tend to engage in short-term trades with holding period of four weeks (or less) despite only breaking-even or making economically insignificant (modest) benchmark-adjusted losses after round-trip transaction costs for liquidity, risk-management, or tax-minimization reasons. Among these, evidence for liquidity trading motive is the strongest.